2017
DOI: 10.1136/bmjopen-2016-012221
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a targeted lifestyle intervention in primary care on diet and physical activity among South Asians at risk for diabetes: 2-year results of a randomised controlled trial in the Netherlands

Abstract: ObjectivesIn South Asian populations, little is known about the effects of intensive interventions to reduce the risk of type 2 diabetes on health behaviour. We examined the effectiveness at 2 years of a culturally targeted lifestyle intervention on diet, physical activity and determinants of behaviour change among South Asians at risk for diabetes.DesignRandomised controlled trial with de facto masking.SettingPrimary care.ParticipantsA total of 536 18- to 60-year-old South Asians at risk for diabetes (ie, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 41 publications
0
25
0
1
Order By: Relevance
“…A first strength of the current study is that specific parenting practices were examined, which gives more insight into parental correlates of children’s screen-time compared to more generally formulated parenting practices (e.g., limit setting, using praise and rewards). Another strength is the focus on a specific vulnerable population, namely families with a higher risk of developing type 2 diabetes, as (intervention) studies focusing on this group can eventually help to prevent or postpone the disease [ 37 ]. Nevertheless, the tight focus on this vulnerable group implies that our findings cannot be generalized to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…A first strength of the current study is that specific parenting practices were examined, which gives more insight into parental correlates of children’s screen-time compared to more generally formulated parenting practices (e.g., limit setting, using praise and rewards). Another strength is the focus on a specific vulnerable population, namely families with a higher risk of developing type 2 diabetes, as (intervention) studies focusing on this group can eventually help to prevent or postpone the disease [ 37 ]. Nevertheless, the tight focus on this vulnerable group implies that our findings cannot be generalized to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient PA can impact considerably on health and productivity and is a cause of many chronic diseases such as coronary heart disease, type 2 diabetes, breast cancer, and colon cancer [1,3,5,6]. Regular PA is a protective factor not only for leading chronic diseases [4] but for a range of important disease risk factors such as hypertension, overweight, and obesity [7]. Recently published evidence shows that there is still over a quarter of the global population who do not undertake recommended levels of PA, and this proportion is higher among women than men [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the China Da Qing Diabetes Prevention Study, the 23-year cumulative incidence of diabetes was 89.9% among controls with an impaired glucose tolerance (IGT) defined with repeated oral glucose tolerance tests (OGTTs) even after a six-year lifestyle intervention [ 5 ]. A large number of trials have demonstrated obvious reductions in the risk of diabetes development among individuals with prediabetes after lifestyle or pharmacological interventions [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Prediabetes can convert back to normoglycemia and diabetes can be prevented by changes in lifestyles.…”
Section: Introductionmentioning
confidence: 99%